Terahertz Generation Using Implanted InGaAs Photomixers and Multi-wavelength Quantum Dot Lasers - Hou, Y.; Liu, J. R.; Buchanan, M.; Thorpe, A. J. Spring; Poole, P. J.; Liu, H. C.; Wu, Ke; Roorda, Sjoerd; Zhang, X. P. (Nano-Micro Letters, 2012)
We report on a study of terahertz (THz) generation using implanted InGaAs photomixers and multi-wavelength quantum dot lasers. We carry out InGaAs materials growth, optical characterization, device design and fabrication, and photomixing experiments. This approach is capable of generating a comb of electromagnetic radiation from microwave to terahertz. For shortening photomixer carrier lifetime, we employ proton implantation into an epitaxial layer of lattice matched InGaAs grown on InP. Under a 1.55 μm multi-mode InGaAs/InGaAsP quantum dot laser excitation, a frequency comb with a constant frequency spacing of 50 GHz generated on the photomixer is measured, which corresponds to the beats of the laser longitudinal modes. The measurement is performed with a Fourier transform infrared spectrometer. This approach affords a convenient method to achieve a broadband multi-peak coherent THz source.